Changes In Regional Language In The Interaction Of The Pulau Terap Village Community - Isratul Jannah; Kasmawarni; Dhea Nanda Heriana (Culture education and technology research (Cetera), 2024)
This study focuses on the preservation of the regional language (OCU language) in the interaction of the Kampar community that occurs in Pulau Terap Village. This language preservation research is carried out so that the position of the Ocu language can be upheld by the Kampar community and to document the language so that it does not experience shift or extinction. This research uses sociolinguistic and qualitative research methods. How people in the past viewed the world and communicated their ideas through language.